2012
DOI: 10.1063/1.4773480
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of effective masses in CuInSe2

Abstract: The effective g-factor in In0.53Ga0.47As/In0.52Al0.48As quantum well investigated by magnetotransport measurement J. Appl. Phys. 113, 033704 (2013) Electron effective mass in n-type electron-induced ferromagnetic semiconductor (In,Fe)As: Evidence of conduction band transport Appl. Phys. Lett. 101, 252410 (2012) Two-site Hubbard molecule with a spinless electron-positron pair J. Appl. Phys. 112, 123706 (2012) Electronic band structure and effective mass parameters of Ge1-xSnx alloys J. Appl. Phys. 112,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 26 publications
0
23
3
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 more stable defect complexes. The radiation damage produced by 10 keV protons implanted in CuInSe 2 single crystal with a dose of 3x10 16 cm -2 has been studied by Rutherford backscattering-channelling [25]. The experimentally estimated concentration of atoms in the indium sub-lattice displaced to interstitial positions was found to be less than 20% of that predicted by TRIM one suggesting that more than 80% of primary defects are healed during or shortly after the implantation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 more stable defect complexes. The radiation damage produced by 10 keV protons implanted in CuInSe 2 single crystal with a dose of 3x10 16 cm -2 has been studied by Rutherford backscattering-channelling [25]. The experimentally estimated concentration of atoms in the indium sub-lattice displaced to interstitial positions was found to be less than 20% of that predicted by TRIM one suggesting that more than 80% of primary defects are healed during or shortly after the implantation.…”
Section: Resultsmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 [16] is significantly greater than that of electron m * h =0.09m e [17]. CuInSe 2 contains both donors and acceptors showing p-type conductivity if the concentration of acceptors is higher than that of donors.…”
Section: Resultsmentioning
confidence: 99%
“…Early optical spectroscopy studies of the excitonic properties of CuInSe 2 revealed the complexity of the valence band, which is split into A, B, and C sub-bands by the simultaneous influence of the non-cubic crystal field and spin-orbit coupling. 5 Recently, the excitonic studies were extended by works based on new advances in the material structural quality [6][7][8][9] determining accurate values of the A and B exciton binding energies E b 7 and hole effective masses. 9 Significantly fewer papers however are concerned with the C exciton, although the C-band parameters are necessary for the development of kp theory in the chalcopyrites.…”
mentioning
confidence: 99%
“…5 Recently, the excitonic studies were extended by works based on new advances in the material structural quality [6][7][8][9] determining accurate values of the A and B exciton binding energies E b 7 and hole effective masses. 9 Significantly fewer papers however are concerned with the C exciton, although the C-band parameters are necessary for the development of kp theory in the chalcopyrites. Only its spectral position 7,10,11 can be found in the literature whereas neither E b nor experimentally determined effective masses have been reported so far.…”
mentioning
confidence: 99%
See 1 more Smart Citation